Novel Rake receiver structure for ultra wideband system based on antenna diversity - QI Li-na; GAN Zong-liang; ZHU Hong-bo (Tongxin xuebao)
A novel receiver structure for TH-UWB wireless communication system was proposed. The improved receiver, combining the antenna diversity with Rake receiver, could enhance the ability to suppress the multi-user interference and multipath fading. Theoretic analysis and simulation results show that the proposed receiver can achieve better performance than the conventional Rake receiver.